2014
DOI: 10.1371/journal.pone.0113620
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adipogenesis of Human Adipose-Derived Stem Cells on Polycaprolactone Fiber Matrices

Abstract: With accelerating rates of obesity and type 2 diabetes world-wide, interest in studying the adipocyte and adipose tissue is increasing. Human adipose derived stem cells - differentiated to adipocytes in vitro - are frequently used as a model system for white adipocytes, as most of their pathways and functions resemble mature adipocytes in vivo. However, these cells are not completely like in vivo mature adipocytes. Hosting the cells in a more physiologically relevant environment compared to conventional two-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
1
26
1
Order By: Relevance
“…This supports previous work purporting the use of PDO scaffolds for adipose stem cell culture . Enhanced differentiation of mesenchymal stem cells on aligned over randomly orientated electrospun scaffolds is also supported on electrospun polycaprolactone scaffolds . However, it has been shown that adipogenic gene expression ( PPARG ) is lower on aligned compared with randomly orientated fibers of electrospun poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate scaffolds .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This supports previous work purporting the use of PDO scaffolds for adipose stem cell culture . Enhanced differentiation of mesenchymal stem cells on aligned over randomly orientated electrospun scaffolds is also supported on electrospun polycaprolactone scaffolds . However, it has been shown that adipogenic gene expression ( PPARG ) is lower on aligned compared with randomly orientated fibers of electrospun poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate scaffolds .…”
Section: Discussionsupporting
confidence: 88%
“…27 Enhanced differentiation of mesenchymal stem cells on aligned over randomly orientated electrospun scaffolds is also supported on electrospun polycaprolactone scaffolds. 28 However, it has been shown that adipogenic gene expression (PPARG) is lower on aligned compared with randomly orientated fibers of electrospun poly(3-hydroxybutyrate-co-3-hydroxyhexanoate scaffolds. 29 This difference was seen when cultured in noninducing but not inducing medium and suggests that fiber orientation-effects on adipogenic differentiation are influenced by the biological milieu.…”
Section: Adipogenic Differentiation Was Best Facilitated By Aligned Pmentioning
confidence: 99%
“…On the other hand, LPL gene expression increased in random‐oriented PCL plates. A study by Brannmark et al found increased gene expression of PPARγ2 and LPL in human adipocytes compared to undifferentiated ADMSCs cells cultured in control, aligned‐, and random‐oriented PCL plates; however, no difference in genes expression were observed between adipocytes cultured in 3‐D compared to control 2‐D plates. In that study, authors have also reported that expression of other adipogenic markers, such as β‐adrenergic receptors1&2 and PPARγ coativator1‐beta in adipocytes were not significantly different compared to undifferentiated cells, and the expression of Adenosine A1 receptor was even downregulated in adipocytes …”
Section: Discussionmentioning
confidence: 96%
“…Compared to 2D culture, 3D culture for adipogenesis in general could: 1) deposit an extensive ECM network (Grayson et al, 2004), 2) recapitulate adipose stem cell microenvironments (Yang et al, 2010), 3) enhance adipogenic differentiation, exhibiting more mature adipogenesis of stem cells (Gerlach et al, 2012), efficient lipid accumulation and in vivo-like organogenesis (Daquinag et al, 2013), expression of adipocyte-specific markers (Hong et al, 2005; Neubauer et al, 2005; Stacey et al, 2009) as well as VEGF (Girandon et al, 2011), and increase secretion of adipokines such as leptin (Kang et al, 2005), 4) be more sensitive to insulin-stimulated glucose uptake and drug treatment (Brännmark et al, 2014; Turner et al, 2014), 5) allow long-term survival (Neuss et al, 2008a), and 6) be feasible to manipulate cellular microenvironments for adipogenesis (Daya et al, 2007). …”
Section: 3d Microenvironments To Control Adipogenesis Of Stem Cellsmentioning
confidence: 99%